2023
DOI: 10.1093/ofid/ofad105
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Duration of Systemic Corticosteroids in Coronavirus Disease 2019 Treatment: A Systematic Review and Meta-analysis

Abstract: Background Corticosteroids confer a survival benefit in individuals hospitalized with COVID-19 that require oxygen. This meta-analysis seeks to determine the duration of corticosteroids needed to optimize this mortality benefit. Methods Electronic databases were searched to March 9, 2022, for studies reporting corticosteroid versus no corticosteroid treatment in hospitalized COVID-19 patients. We estimated the effect of corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…Таким образом, в соответствии с нашими данными, а также данными других исследований оптимальная длительность использования ГК не должна превышать 7 сут. [17,[29][30][31].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Таким образом, в соответствии с нашими данными, а также данными других исследований оптимальная длительность использования ГК не должна превышать 7 сут. [17,[29][30][31].…”
Section: Discussionunclassified
“…P. Ssentongo на основе результатов исследования [17], выполненного на 13 404 пациентах, сделал вывод, что оптимальная продолжительность применения ГК у пациентов с COVID-19 тяжелого течения должна составлять до 6 сут., поскольку при лечении длительностью более 7 сут. отсутствует дополнительная польза от терапии и улучшение выживаемости пациентов.…”
Section: Covid-19unclassified
“…The WHO announced that only patients with severe or critical symptoms of COVID-19 should be administered dexamethasone (or other corticosteroids such as prednisolone and hydrocortisone), reiterating that mild cases do not benefit from the treatment [180]. This evidence comes from combined results of clinical trials that showed that deaths were reduced by 20% when patients with severe COVID-19 were given corticosteroid treatment during their illness, thus confirming the efficacy of corticosteroids during the hyperinflammatory stage of SARS-CoV-2 infection [181].…”
Section: Other Agents and Therapiesmentioning
confidence: 99%